Estudo de excitações tipo strings em gelos de spin artificiais através de cadeias lineares de dipolos magn/eticos - Denis da Mata Oliveira (2014)
In this work we study a system of classical magnetic Ising-like dipoles (spins) on the square lattice interacting exclusively by magnetic dipolar interaction. The spins are positioned in sequence, forming linear chains on the lattices links (strings), parallel to its plane, through self-avoiding walks. Our aim is to better understand the behavior of collective excitations that behave as magnetic monopoles in artificial spin ice systems, since they resemble the chains studied here. We observe a very rich behavior of these structures with the presence of signs of phase transitions and a non-trivial behavior with chain length. We also present some results for the hexagonal lattice. We observed that the low temperature properties of the square lattice are determined by configurations that satisfy a rule of alternation in the direction of the walk, while in the hexagonal lattice the minimum end-to-end distance is the key factor.